Co-pyrolysis of empty fruit bunches impregnated with Ni and lignite into liquid oil. (2022) - Sunarno,; Zafirah, Nada; Agustin, Tesa; Reni Yenti, Silvia; Wisrayetti,; Herman, Syamsu; Bahri, Syaiful
Abstract: Oil produced from biomass pyrolysis is a potential fuel and can be used to overcome the energy crisis. However, this oil cannot replace transportation fuel because of its low calorific value. To improve the quality of oil, biomass pre-treatment and co-pyrolysis process were carried out. This study aimed to determine the influence of empty fruit bunches (EFB) pre-treatment using Ni(NO3 )2 solution, the ratio of pretreated EFB and lignite, and the influence of the ratio CaO catalyst/raw material on yield and quality of liquid oil. EFB pre-treatment was performed by impregnation of EFB with Ni(NO3 )2 solution at various concentrations of 0.1, 0.3, and 0.5 M at 25 °C for 24 h. The co-pyrolysis process was carried out at 400 °C and nitrogen gas was flowed with a flow rate of 100 mL/min for 50 min with various pre-treated EFB, the ratio of raw material EFB/lignite (100/0, 25/75, 50/50, 75/25, 0/100), and the ratio of CaO catalyst/raw material (2%, 5%, 8% w/w). The best liquid oil produced is from EFB pre-treatment using Ni(NO3 )2 0.3 M at a raw material ratio of 75/25 EFB/lignite with the addition of 8% CaO catalyst with a yield of 32.3%, which has a density of 1.049 g/mL, the viscosity of 3.47 cSt, the heating value of 36.63 MJ/kg, and the pH of 2.5 with a liquid oil composition of 11.52% acetic acid, 0.47% phenol, 14.7% aldehydes, 46.9% alkane and 16.83% alkene.